Investigation of the photocatalytic degradation pathway of the urine metabolite, creatinine: the effect of pH - Antoniou, Maria G.; Nambiar, Usha; Dionysiou, Dionysios Demetriou (My University, 2009)
This study investigated the degradation pathway of creatinine (a urine metabolite) with immobilized titanium dioxide photocatalysts. The degradation of creatinine was studied at three different pH values (acidic, neutral and basic) in the absence of buffering solutions. The intermediates formed were identified by using electrospray ionization mass spectrometer (ESI-MS) in both negative and positive ion mode. Two distinct mechanistic pathways which govern the photocatalytic degradation of creatinine irrespective of the pH of the initial solution were identified. The initial solution pH affected only the selectivity between the two mechanisms. The primary oxidation steps of creatinine with hydroxyl radicals included demethylation, hydrogen abstraction, hydroxylation, oxidation, and ring opening. At acidic pH, additional transformation steps of the two mechanisms were identified. The intermediates detected in the positive ion mode, contained at least one atom of nitrogen in their structure, explaining the observed low nitrogen mineralization of creatinine with TiO2 photocatalysis. The intermediates in the negative ion mode were low molecular weight organic acids that contained only carbon and hydrogen atoms.
Keywords: Creatinine; Guanidine derivatives; Intermediates; Mass spectrometry; Photocatalytic; TiO2 photocatalysis; Treatment; Urine metabolites; Wastewater